NUMERICAL VIBRATION ANALYSIS OF THE DAM SECTOR GATE STRUCTURE WITH CONSIDERATION TO MATERIAL DEGRADATION CHARACTERISTICS - Ghazali M.H.M.; Mazlan A.Z.A.; Azman M.A.; Zawawi M.H. (Taylor's University, 2023)
Vibration characteristic is one of the important criteria that need to be investigated regularly for the reliability of the dam structure. As the dam material is degraded over the years, the vibration characterization must be performed to investigate the effect of material degradation to the structural vibration. This study shows a detail 3D numerical vibration analysis of the dam sector gate section in terms of natural frequencies, mode shapes and frequency response function (FRF) with consideration to the material degradation characteristics. The real dam concrete materials are extracted from the site and tested to determine the degraded youngs modulus value of the materials. The degraded youngs modulus value is then compared with the original value using modal and harmonic response analyses for both experimental and simulation. From the study, the percentage of material degradation shows a significant value, which is 61.56 % of natural frequency value changes over 40 years period. The results in terms of natural frequencies, mode shapes and FRF are compared for both original and degraded materials of the dam structure. A maximum of 80.98 % difference is observed at the third mode shape, whereby the maximum deformation of the degraded concrete is more than double of the original concrete. This result is important for the dam management as reference to any flow-induced vibration phenomenon and future development of condition-based monitoring (CBM) system. School of Engineering, Taylors University.